Relationship of endogenous antioxidant levels with metabolic control parameters in diabetic infantile-juvenile patients - Pérez Álvarez, Yohanka; Díaz Calzada, Marvelia; Montier Iglesias, Ariel; Fuentes de la Rosa, Yazuina; Roque Acanda, Kenia; Rodríguez Sardiñas, Lázara Maidelys (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
Introduction: diabetes mellitus is one of the pandemics of the present century that severely affects the infantile-juvenile population, due, among other factors, to poor nutritional habits. Objective: to test the changes in the levels of endogenous nucleophilic antioxidants in relation to control parameters in patients with infantile-juvenile diabetes. Material and Method. Of the 138 patients with infantile-juvenile diabetes who attended the provincial consultation at the Specialties Polyclinic of the Provincial Pediatric Hospital ¨Pepe Portilla¨ in the period from March 2019 to June 2020, 28 patients were chosen by means of a purposive sampling. The following variables were collected: age, sex, weight and height for calculation of body mass index, fasting blood glucose, HbA1c, albumin and uric acid. Absolute and relative frequency were used for qualitative variables and mean, standard deviation and median for quantitative variables. When the non-normal distribution of the data was found by the Shapiro-Wilk test, Spearman's correlation coefficient was used with a level of certainty of 95% to evaluate the relationship between the quantitative variables.  Results. Glycemia showed no correlation with either serum albumin or uric acid values. A positive and statistically significant correlation was found between HbA1c values with serum albumin and uric acid (p